Conspecific leaf litter induces negative feedbacks in Asteraceae seedlings. Issue 12 (4th November 2021) - Zaret, Max M.; Bauer, Jonathan T.; Clay, Keith; Whitaker, Briana K.
Abstract: The plant soil feedback (PSF) framework has been instrumental in understanding the impacts of soil microbes on plant fitness and species coexistence. PSFs develop when soil microbial communities are altered due to the identity and density of a particular plant species, which can then enhance or inhibit the local survival and growth of that plant species as well as different plant species. The recent extension of the PSF framework to aboveground microbiota, termed here as plant phyllosphere feedbacks (PPFs), can also help to determine the impact of aboveground microbes on plant fitness and species interactions. However, experimental tests of PPFs during early plant growth are nascent and the prevalence of PPFs across diverse plant species remains unknown. Additionally, it is unclear whether plant host characteristics, such as functional traits or phylogenetic distance, may help to predict the strength and direction of PPFs. To test for the prevalence of litter‐mediated PPFs, recently senesced plant litter from 10 native Asteraceae species spanning a range of life history strategies was used to inoculate seedlings of both conspecific and heterospecific species. We found that exposure to conspecific litter significantly reduced the growth of four species relative to exposure to heterospecific litter (i.e., significant negative PPFs), three species experienced marginally significant negative PPFs, and the PPF estimates for all 10 species were negative. However, neither plant functional traits, nor phylogenetic distance were predictive of litter feedbacks across plant species pairs, suggesting that other mechanisms or traits not measured may be driving conspecific negative PPFs. Our results indicate that negative, litter‐mediated PPFs are common among native Asteraceae species and that they may have substantial impacts on plant growth and plant species interactions, particularly during early plant growth.